The Quality of Sexed Bali Bull Semen Using Percoll Density Gradient Centrifugation in Various Gradients with Tris Aminomethane Diluent - Rahmawati, Nanda Ayu; Yekti, Aulia Puspita Anugra; Wahyudi, Aditiya; Nafis, Fardha Ad Durrun; Isnaini, Nurul; Susilawati, Trinil (Jurnal Ilmu-Ilmu Peternakan, 2025)
This research aims to determine the quality of spermatozoa in the sexed semen that separated using the Percoll Density Gradient Centrifugation (PDGC) method with various gradients using egg yolk tris aminomethane diluent. The study was conducted at the Singosari Artificial Insemination Center from December 2023 to February 2024. The study's material was the semen of one Bali bull with individual motility ? 70%. The experimental design used a Randomized Group Design with the sexed semen PDGC method treatment: T1 = 10 gradients, T2 = 5 gradients, and T3 = 3 gradients, each with ten replications. The analysis showed that the gradient variations significantly impact the individual motility on the bottom layer of sexed semen (P<0.05). Conversely, gradient variance did not affect viability, abnormality, concentration, total motile spermatozoa, and individual motility on the top layer of sexed semen (P>0.05). In conclusion, sexed semen using the PDGC method with varied gradients is suitable for the freezing process due to its high quality.